Hemingway : the writer's art of self-defense - Benson, Jackson J. (University of Minnesota Press, 1969)
In a close critical analysis of five of Ernest Hemingway's novels and a number of his most important short stories, Professor Benson provides a fascinating new view of his work. The novels discussed are The Sun Also Rises, A Farewell to Arms, For Whom the Bell Tolls, Across the River and into the Trees, and the Old Man and the Sea. Hemingway's art of self-defense, which Professor Benson refers to in his subtitle, was, as he demonstrates in his perceptive criticism, the writer's use of style and technique to attack the sentimentalities which were Hemingway's own weakness. Emotion was central to the task which Hemingway defined for himself, Professor Benson explains, and a critical appraisal of his work must, therefore, focus particularly on the ways in which he dealt with and expressed emotion.